Microbial Resistance to Carbapenems in Effluents from Gynaecological, Paediatric and Surgical Hospital Units - El hassan Loumame; Abdessamad Tounsi; Soumia Amir; Nabila Soraa; Naaila Ouazzani (MDPI AG, 2022)
The aim of this work is to identify and count antimicrobial resistance (AMR) in hospital effluents (HEs) of 2 units of the University Hospital Mohamed VI the Mother and Child Hospital (MCH) and the Ar-razi Surgical Hospital (ArzH), and to compare the two hospital units in terms of ARMs and seasonal variation. Each HE was sampled during 2016 and 2017. After identification of the pathogenic strains and determination of AMR, the results were reported for 24 ABs, including 3 carbapenems (CBP), and their consumption rates. The Predicted environmental concentration (PEC) rate of carbapenems in the HE of the study sites is calculated. A comparative analysis of the AMR of the isolated bacterial species was performed and related to the evolution of PEC in HEs. In the ArzH effluents:15 strains isolated, 7 are carbanepenem-resistant Enterobacteria (CRE) and are resistant to at least one of the 3 carbapenems tested. ArzH and MCH effluents respectively show some similarities: 26.87% and 28.57% of isolated bacteria are resistant to ertapenem while 43.48% and 57.14% are resistant to meropenem. However, for imipenem, the MCH effluent has a higher percentage of bacterial antibiotic resistance than ArzH. In addition, the percentage of resistance in each hospital unit effluent is mainly in relation with the increasing antibiotic consumption and predicted environmental values PEC for very antibiotic in each unit in the same period.